Nonlinear wave modulation in thick elastic tube contained with inviscid fluid - Ahmad, Nur Fara Adila; Choy, Yaan Yee; Tay, Kim Gaik (2018)
In this research, we are focused on mathematical modeling for blood flows in an elastic artery. We considered the blood as an incompressible inviscid fluid and treated the artery as an incompressible, isotropic and thick elastic tube. The modulation of nonlinear wave modulation wave in thick elastic tube filled with inviscid fluid is studied. By using reductive perturbation method, we obtained the Nonlinear Schrodinger (NLS) type equation as the evolution equation for the corresponding mathematical model.